Public diplomacy at home : domestic dimensions - Huijgh, Ellen (Diplomatic studies, 2019)
"This book is about the domestic dimension of public diplomacy, which must be understood within the context of public diplomacy's evolution over time. In the virtually connected world of today, newcomers such as supranational organizations, sub-states and Asian countries have had less difficulty than Western nation-states including a domestic dimension in public diplomacy. Doing so does not separate the domestic and international components; rather, it highlights that there is a holistic/integrative approach to public involvement at home and abroad. In Huijgh's comprehensive analysis, including case studies from North America, Europa and the Asia-Pacific, public diplomacy's international and domestic dimensions can be seen as stepping stones on a continuum of public participation that is central to international policymaking and conduct"--